1982
DOI: 10.1093/bja/54.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Sore Throat After Operation: Influence of Tracheal Intubation, Intracuff Pressure and Type of Cuff

Abstract: One hundred and eighty-four patients were studied to elucidate the contribution of intracuff pressure and cuff type to the occurrence of sore throat and hoarseness after operation. The patients were allocated to one of the following groups: A = mask only; B = reusable Rüsch tube with intermittent cuff volume adjustment; C = reusable Rüsch tube without cuff volume adjustment; D = disposable Portex Blue Line tube with intermittent cuff volume adjustment; E = disposable Shiley Low Pressure tube with intermittent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
2
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 14 publications
7
67
2
2
Order By: Relevance
“…The incidence of sore throat in the LMA group (12%) is similar to that reported by Brodrick [10] and slightly higher than the 6-8% reported by others [11,12]. These data are comparable with the incidence of sore throat in anaesthetised unintubated patients [13]. The incidence of sore throat does appear to decrease with increased clinical experience in using the LMA [7].…”
Section: Discussionsupporting
confidence: 85%
“…The incidence of sore throat in the LMA group (12%) is similar to that reported by Brodrick [10] and slightly higher than the 6-8% reported by others [11,12]. These data are comparable with the incidence of sore throat in anaesthetised unintubated patients [13]. The incidence of sore throat does appear to decrease with increased clinical experience in using the LMA [7].…”
Section: Discussionsupporting
confidence: 85%
“…Christinestock & John Downs [3] found no significant difference in the incidence or severity of sore throats based on the type of lubricant used on the tracheal tube or based on the presence or absence of lignocaine in the lubricant. In fact there was no difference in the incidence or severity of sore throat in patients who were intubated with dry tubes compared with those intubated with lubricated tubes [2].…”
Section: Use Of Lubricantsmentioning
confidence: 83%
“…b) Bulkier and larger low pressure tubes produce more damage to upper airway structures on intubation or extubation c) Low pressure high volume tube cuffs produce grooves in the mucosa because of wrinkling of the cuffs as it is inflated, unlike the inflation of high pressure low volume cuffs [16]. Edward loeser et al [11] demonstrated that low pressure high volume endotracheal tube cuffs IJBR (2015) 6 (07) www.ssjournals.com…”
Section: Low Pressure High Volume Cuff Tubes Verses High Pressure Lowmentioning
confidence: 99%
See 2 more Smart Citations